Evaluation of marking efficiency of different alizarin red S concentrations on body fish structures in Oreochromis niloticus (Perciformes: Cichlidae) juveniles - Ana L. Ibáñez; Antonio Rodríguez-Canto; Jasmín Cortés-Martínez; José L. García-Calderón (Revista de Biología Tropical, 2013)
The use of alizarin red S (ARS) marked tilapias could provide valuable fisheries management information to evaluate fish stocking events and may facilitate aquaculture management practices. As a new technique in fishes, the aim of this study was to compare and evaluate the chemical marks produced in tilapia juveniles by ARS through two treatments: 1) 12 hours of immersion and 2) immersion after osmotic induction. This was analyzed at three concentrations: 50, 75 and 100mg/l, and in three structures: otoliths, fish scales and caudal fin rays of Oreochromis niloticus juveniles. After three culture months 80% of specimens were analyzed and significant differences (p<0.05) in mark intensity were detected between treatments for otoliths and fin rays, but not for fish scales. Significant differences between concentrations were found for the 12h immersion treatment, while no significant differences were detected with osmotic induction. Our results showed that marks appeared at all concentrations, and none of the concentrations produced weak marks. Osmotic induction had a greater mortality than the 12h immersion procedure. After eight culture months the rest of the specimens were analyzed and the mark permanence was observed in all cases. According to the present results we recommend the marking process of 12h immersion treatment at 100mg/L concentration. El uso de alizarina roja S (ARS) para marcar tilapias podría proporcionar información valiosa para el manejo de su pesquería. Para evaluar pesquerías acuaculturales manejadas con siembras o repoblamientos de peces se comparó y evaluó la marca producida por la alizarina roja S, empleando dos tratamientos: 1) Inmersión en ARS durante 12h; e 2) Inmersión en ARS después de un choque osmótico. El análisis se realizó a tres concentraciones: 50, 75 y 100mg/l y en tres estructuras: otolitos, escamas y radios de la aleta caudal de Oreochromis niloticus. Ochenta por ciento de los ejemplares fueron cultivados durante tres meses y analizados posteriormente. Los resultados mostraron diferencias entre las concentraciones de la marca para el tratamiento de 12h de inmersión mientras que no hubo diferencias entre las concentraciones para el tratamiento con inducción osmótica. Se encontraron diferencias en la intensidad de la marca entre los tratamientos para otolitos y radios de las aletas pero para las escamas no hubo diferencias significativas. Todas las concentraciones produjeron marcas (desde débiles a intensas), sin embargo la concentración de 100mg/l no produjo marcas débiles. El tratamiento por inducción osmótica presentó mayores niveles de mortalidad. Después de ocho meses de cultivo el resto de los ejemplares fueron analizados y se observó la permanencia de las marcas en todos los casos. En vista de lo anterior, para los propósitos de marcaje se recomienda el uso del tratamiento de inmersión por 12h y una concentración de 100mg/l.